Amelioration of lower limb pain and foot drop with 10 kHz spinal cord stimulation: A case series. Issue 5 (May 2021) - Feng, Honghui; Doherty, Patrick; Rotte, Anand; Bovinet, Christopher
There are limited treatment options for patients with foot drop and associated lower back and/or leg pain. We present a case series of three patients who received permanent implantation of 10 kHz spinal cord stimulation (10 kHz SCS) devices. Following treatment, all patients reported sustained improvements in lower back and leg pain, foot mechanics and function which resulted in increased mobility and cessation of opioid use for pain management. Patients were followed up for approximately four years. Treatment with 10 kHz SCS may be a promising alternative to other interventional procedures commonly used for these patients.